Undak Usuk Basa as a Reflection of Social Hierarchy in Sundanese Communication - Salsa, Salsa Bila Az Zahra; Abdullah, Mirna Nur Alia; Morimoto, Elisabeth; Wilodati, Wilodati (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2025)
Background: Undak Usuk Basa, the system of speech levels in Sundanese society, functions not only as a medium of communication but also as a representation of social hierarchy and politeness. This study contributes by highlighting the socio-pragmatic functions of Undak Usuk Basa in the modern context, an aspect often overlooked in previous research that has predominantly focused on its decline.Purpose: The purpose of this research is to analyze how Undak Usuk Basa encodes social hierarchy and how modern social changes influence its patterns of use.Method: The method employed is a literature study, analyzing 25 selected articles out of an initial 45 obtained from databases such as ScienceDirect, Garuda, Google Scholar, Sinta, and DOAJ, covering publications from the past decade. The selection process was based on criteria of topical relevance, credibility, and both theoretical and empirical foundations.Results: The findings reveal that Undak Usuk Basa regulates language choice based on age, social status, and interpersonal relations, making it an essential instrument for maintaining social harmony. However, globalization, urbanization, and the penetration of digital media have fostered more egalitarian and practical communication patterns, particularly among younger generations, leading to a decline in the use of speech levels.Theoretical implication: The study affirms that linguistic hierarchy functions as cultural capital, reflecting and sustaining social structures.Practical implication: The findings suggest the need for preservation through education, digital media, and cultural programs.